Misi Gereja di Tengah Pluralitas Agama dan Budaya - Hariprabowo, Y. (Jurnal Orientasi Baru, 2009)
Modern society is marked by an increasing plurality at any sphere. Amongbelievers of great religious traditions, pluralism is a blessing as well as a realchallenge. Many religions imply truth claims and theological dogma which areabsolute in character. On the other hand, most of them are missionary bodyof religions. Christianity itself is very apostolic. The existence of the Churchis for mission (Matt 28:19), to bring the Good News of love and liberation,embodied in Jesus Christ. Within a pluralistic society, this mission will not beautomatically welcomed. There are people with different religious believes andmany were neither born Christian nor introduced ever to Jesus Christ. Withinthis pluralistic reality, evangelization rightly characterized by humility, mutuallistening and respect for different religious and cultural values. Religiousdialogue is a matter of urgency especially to discern constructively commonvalues such as justice, mercy and peace for the betterment of human society.Method of contextual theology needs to be employed to promote a theologyof mission with emphasis on inclusive Reign of God and reconciliation.